OP0246 Increased Prevalence of Periodontal Disease in Anti-CCP Positive Individuals at Risk of Progression To Inflammatory Arthritis: A Target for Prevention?. (15th July 2016) - Mankia, K.; Hunt, L.; Hensor, E.; Nam, J.; Clerehugh, V.; Speirs, A.; Tugnait, A.; Do, T.; Devine, D.; Emery, P.
Abstract : Background: The prevalence of periodontal disease is increased in rheumatoid arthritis (RA) patients (1) but has not been reported in seropositive at risk individuals. Comprehensive periodontal examination requires expert evaluation of six sites per tooth for bleeding on probing (BOP), clinical attachment loss (CAL) and pocket depth (PD). Periodontal disease is associated with Porphyromonas gingivalis, which, through its unique ability to citrullinate arginine residues (2) may trigger RA-related mucosal autoimmunity. Salivary IgA anti-CCP antibodies have been reported in RA patients (3) but their presence in at risk individuals has not been described. Objectives: To investigate the prevalence of periodontal disease and to describe evidence of RA-related mucosal autoimmunity in anti-CCP positive subjects at risk of progression to inflammatory arthritis. Methods: Anti-CCP positive individuals with no evidence of synovitis (CCP+), healthy controls (HC) and anti-CCP positive RA patients were recruited. All patients underwent periodontal examination by a dentist; six sites per tooth were assessed for BOP (present/absent), CAL (mm) and PD (mm). Dentists later agreed a consensus clinical diagnosis for each case, blinded to patient group. Unstimulated saliva and serum samples were collected. CAL≥2mm and PD≥4mm at the same site signified periodontal disease (PDD). The % of evaluable sites with BOP (%BOP) and % with PDD (%PDD) were calculated per patient. Anti-CCP antibodies (anti-CCP2; immunocap assay, Phadia) were measured in paired saliva & serum samples. IgA anti-CCP titres exceeding the 95th centile in HCs were considered positive. Mann-Whitney U tests were used to compare groups. Spearman rho is reported for associations. Results: We recruited 31 CCP+, 20 HC and 12 RA patients. Groups were balanced for sex, smoking and number of missing teeth. Dentists classified 77% of CCP+ and 45% of HC as having clinical periodontal disease. %BOP was higher in CCP+ than HC (CCP+=26.9 [8.6, 46.3], HC=9.8 [3.1, 17.9]; p=0.033) (fig 1 a). %PDD was higher in CCP+ compared to HC (CCP+=1.9 [0.0, 15.7], HC=0.3 [0.0, 1.4]; p=0.050) (fig 1 b). PDD was recorded at ≥1 site in 65% of CCP+ and 50% of HC. Similar results were obtained for percentage of sites with both PDD and BOP present. 4 patients (CCP+ n=3, RA n=1) had positive saliva IgA anti-CCP results (>6μg/L). 21% of CCP+ (n=6) and 17% of RA (n=2) had positive serum IgA anti-CCP results (>15μg/L); these were not associated with periodontal disease measures. RA patients were slightly older (mean age CCP+=52, HC=50, RA=62) and on disease-modifying treatments; the latter may account for similar %BOP and lower %PDD in this group compared to HC. Age was not associated with %BOP (rho=0.05, p=0.714) or %PDD (rho=0.03, p=0.833). Conclusions: We provide preliminary evidence of both an increased prevalence of periodontal disease and the presence of salivary IgA anti-CCP antibodies in anti-CCP positive individuals at risk of arthritis development. These findings support the concept that periodontal inflammation precedes joint inflammation as a potential trigger or early target of RA-related autoimmunity. References: A Abou-Raya et al. Scan J Rheum, 2005. W McGraw et al. Infect Immun, 1999. A Svard et al. Immunobiology, 2013. Disclosure of Interest: K. Mankia: None declared, L. Hunt: None declared, E. Hensor: None declared, J. Nam: None declared, V. Clerehugh: None declared, A. Speirs: None declared, A. Tugnait: None declared, T. Do: None declared, D. Devine: None declared, P. Emery Consultant for: Pfizer, Abbvie, Roche, MSD, BMS, Novartis, Samsung, Lilly, Sandoz, UCB